THE BENEFITS OF READING PROFESSIONAL ARTICLES FOR CONTINUOUS PROFESSIONAL DEVELOPMENT OF LANGUAGE TEACHERS - Kukibayeva, Mahliyo (Журнал иностранных языков и лингвистики, 2021)
Current articles outlines the benefits of reading professional articles for the purpose of professional development of EFL teachers in secondary and higher educational level and suggests some useful strategies to professional and personal growth.